Kinesiophobia and Related Factors in Postmenopausal Women with Osteoporosis and Osteopenia - Salim Mısırcı; Yeşim Akyol; Yasemin Ulus; Ahmet Kıvanç Cengiz; Ayhan Bilgici (Galenos Yayinevi, 2021)
Objective:To investigate level of kinesiophobia and related factors in postmenopausal women with osteoporosis (OP) and osteopenia (OPN).Materials and Methods:A total of 60 female patients with postmenopausal OP, 60 female patients with postmenopausal OPN and 60 age- and gender-matched controls were enrolled in this study. Demographic data (age, weight, height, body mass index, educational level, employment status, disease duration and menopause duration) of the participants were recorded. In all participants, the level of kinesiophobia, fear of falling, psychological status, health-related quality of life and osteoporosis self-efficacy were evaluated using the Tampa scale of kinesiophobia (TSK), falls efficacy scale-international (FES-I), hospital anxiety and depression scale (HADS), quality of life questionnaire of the European Foundation for Osteoporosis-41 (QUALEFFO-41) and osteoporosis self-efficacy scale (OSES), respectively.Results:Postmenopausal patients with OP and OPN had higher levels of kinesiophobia than controls (p<0.05). However, there was no difference between the levels of kinesophobia in patients with OP and OPN (p>0.05). In addition, a positive correlation was found between TSK score and FES-I, HADS, QUALEFFO-41 scores and duration of menopause, and a negative correlation between OSES scores in patients with OP and OPN (p<0.05). Patients were divided into two groups according to their kinesiophobia levels: High and low kinesiophobia groups. All clinical parameters were negatively affected in patients in the high kinesophobia group (p<0.05).Conclusion:Both OP and OPN may cause kinesiophobia in postmenopausal women. Increased fear of falling, impaired psychological status, poor quality of life, decreased perception of self-efficacy and prolonged duration of menopause in postmenopausal women with OP and OPN seem to be associated with a higher level of kinesiophobia. As physical activity is essential for bone health, postmenopausal women with OP and OPN should be counselled about the importance of overcoming kinesiophobia.